Strategi Coping Stres Mahasiswa Bimbingan dan Konseling dalam Menyusun Skripsi di Universitas PGRI Sumatera Barat - Utari Reyeki; Yasrial Chandra; Citra Imelda Usman (Kartika: Jurnal Studi Keislaman, 2026)
This research is motivated by the high level of stress experienced by students of the guidance and counseling study program in the thesis preparation process. The purpose of this study is to describe: 1) a stress coping strategy that focuses on problem-focused coping, and 2) a stress coping strategy that focuses on emotion-focused coping. The method used in this study is qualitative descriptive with two key informants, namely (TA) and (AD), as well as four additional informants consisting of each student's supervisor, namely (JA) and (S), as well as close friends of each student, namely (NJS) and (DS). The research instrument uses an interview format, while the data analysis technique is carried out through data reduction, data presentation, and conclusion drawn. The results of the study showed: 1) a stress coping strategy that focuses on problem solving is carried out by students through efforts to overcome thesis problems directly as a form of problem-focused coping. 2) Stress coping strategies that focus on managing emotions are carried out by students through efforts to manage emotional stress during thesis preparation as a form of emotion-focused coping. The results of this research are recommended to students in order to improve discipline in managing time and reduce the habit of delaying revision work so that the thesis preparation process can run more directed and consistently